2009
DOI: 10.1016/j.envint.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the estimated dietary intake of PCDD/Fs and levels in blood in a Flemish population (50–65 years)

Abstract: Dioxin-like activity was measured in the serum of 1425 Flemish men and women via the CALUX assay. The adults, aged between 50 and 65 years, participated in a large biomonitoring program, executed by the Flemish Center of Expertise for Environment and Health between 2002 and 2006. Within the context of this biomonitoring program also dietary intake of dioxin-like contaminants was assessed through a food frequency questionnaire. The relation between the estimated dietary intake and the dioxin-like activity in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Similarly, a cross-sectional analysis of children in Germany also found an inverse association between serum PCBs and body weight (Link et al 2005). Typically, higher BMI for adults is associated with higher serum concentrations of these compounds (Bilau et al 2009; Collins et al 2007; Michalek et al 1996). However, in a follow-up analysis of the Seveso cohort, neither BMI nor percent body fat was associated with serum dioxin concentrations after adjustment for sex (Landi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a cross-sectional analysis of children in Germany also found an inverse association between serum PCBs and body weight (Link et al 2005). Typically, higher BMI for adults is associated with higher serum concentrations of these compounds (Bilau et al 2009; Collins et al 2007; Michalek et al 1996). However, in a follow-up analysis of the Seveso cohort, neither BMI nor percent body fat was associated with serum dioxin concentrations after adjustment for sex (Landi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it has explicitly been shown that if HBM is combined with ambient monitoring and questionnaire data, exposure sources can be identified (e.g. Bilau et al, 2009;Kolossa-Gehring et al, 2012;Cerna et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…of the participants is collected. As this type of information relates to the individual's exposure profile, it is very relevant in the interpretation of an individual's biomarker profile as well (Bilau et al, 2009;Haug et al, 2011;Johansson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The human biomonitoring project investigates the very complex relation between environmental pollution and human health by measuring some selected pollutants and certain health effects in human beings, using biomarkers. (Bilau et al 2009;Schroijen et al 2008) and social scientific research (Keune et al, 2008a).…”
Section: The Centre Of Expertise For Environment and Health (Ceh)mentioning
confidence: 99%